The Concerns, Roots, and Challenges of Islamic Culture in Sumbawa and Their Implications for Implementing Halal Tourism - Jazadi, Iwan; Widari, Iga (Institut Agama Islam Negeri Madura, 2019)
This article analyzes the concerns, roots, and challenges to Sumbawa culture, aiming to inform decisions in designing halal tourism policy in Sumbawa and West Sumbawa Regencies. The theories underpinning this study are that of culture, cultural approaches in foreign language teaching, and halal tourism. The data for analysis come from documentation and observation. The results and discussion show that the present state of Sumbawa culture is at risk of loss or distortion unless its revitalization is committed. The cultural roots identified and analyzed are the ancestorsâ€™ cultures, historical Islamic cultures, and prominent values in social interaction by Sumbawa people. A future challenge to Sumbawa culture lies in the handing down of cultural values by ensuring the fulfilment of the peopleâ€™s right to quality education at all education channels,Â accomodating the rooted cultural values into the educational content, and implementing halal tourism as a means of socialization among Sumbawa people and with guests from other regions or overseas.